Progestins of today and tomorrow. Issue 6 (19th December 2022) - Liu, Serena; Kciuk, Olga; Frank, Madelyn; Tyson, Nichole
Abstract : Purpose of review: To review the current literature on the multiple types and uses of progestins in reproductive healthcare. Recent findings: Progestins for contraceptive use are available in multiple forms, with the ongoing development of transdermal, intravaginal, and male contraception formulations. Noncontraceptive use of progestins often overlaps with contraceptive indications, which allows for simultaneous multipurpose progestin use, especially in reproductive-aged patients. More studies are needed to determine contraceptive doses of progestins used for noncontraceptive purposes. Side effect profiles of progestins are dependent on their formulation and cross-reactivity with other steroid receptors. Development of newer progestins includes manipulating pharmacologic properties to avoid undesired side effects. Summary: Progestins have multiple uses in reproductive healthcare, including contraception, menstrual suppression, endometrial protection, and hormonal replacement therapy. The development of progestins for these indications can expand therapy for people with contraindications to estrogen-based hormonal therapy.